Histopathological Assessment of Orchidectomy Specimens in a Tertiary Care Center - Latheef, Dr. Ali Abdul; Nayak, Dr. Ramdas; Nuzhath, Dr. Taqiya; Shetty, Dr Priyanka P.; Nair, Dr. Vineeth G. (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Orchidectomy is a medical procedure to remove one or both testicles in males.The testis can be removed for torsion/infarction,infection,therapeutic castration for prostate cancer,cryptorchidism and tumor.In our study we did a histomorphological study these lesions which is a rare surgery other than therapeutic purpose. Aims & Objectives: The aim of our study was to emphasise the clinical, radiological and histomorphological features of the rare orchiectomy procedure in various conditions of testis and to find out the clinical relevance. Materials & Methods: This was a retrospective and prospective analysis done for 18 months (January 2016-June 2017). All orchidectomy specimens received in the Department of Pathology were analyzed with respect to clinical indications,radiology,morphology and microscopic features. Results: Out of a total of 23 orchidectomy cases 16 were unilateral and 7 bilateral.Most common age group was 50 to 70 years(13).The youngest and eldest patients were 6 & 89 years respectively.The most common etiology was therapeutic(7 cases of carcinoma prostate ), torsion in 6,epididymo-orchitis in 3,benign tumours in 2,inflammtory causes in 3 and one case of cryptorchidism. Conclusion: Our study helped us to assess and evaluate the clinical relevance of orchidectomy by histomorphological study of these lesions and to defer the procedure in certain non-tumoral cases for the benefit of the patient.